2002
DOI: 10.1038/sj.leu.2402373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methotrexate polyglutamates on thioguanine nucleotide concentrations during continuation therapy of acute lymphoblastic leukemia with mercaptopurine

Abstract: Methotrexate is widely administered with mercaptopurine, a prodrug requiring activation into thioguanine nucleotides (TGN) to exert antileukemic effects. In vitro, methotrexate enhances TGN formation, but in vivo, such enhancement has yet to be demonstrated. We investigated whether TGN concentrations were related to methotrexate concentrations in children with acute lymphoblastic leukemia who received a weekly intravenous methotrexate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
(40 reference statements)
3
22
0
1
Order By: Relevance
“…Alternatively, the subsequent elevation in RBC MTXPG [3][4][5] likely reXected the pulsative release of MTXPG incorporated in bone marrow erythroid progenitors. Interestingly, the median RBC MTXPG 1-5 levels measured at the initiation of the last HDMTX course was 20 pmol/10 9 cells, and these values are similar to those reported in RBC from children receiving weekly MTX dosages 125-fold lower (40 mg/m 2 : 29 pmol/10 9 cells) [9]. We explain these results by rate-limiting FPGS activity in marrow progenitors rather than saturation of MTX uptake (which is passive at higher dose MTX).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Alternatively, the subsequent elevation in RBC MTXPG [3][4][5] likely reXected the pulsative release of MTXPG incorporated in bone marrow erythroid progenitors. Interestingly, the median RBC MTXPG 1-5 levels measured at the initiation of the last HDMTX course was 20 pmol/10 9 cells, and these values are similar to those reported in RBC from children receiving weekly MTX dosages 125-fold lower (40 mg/m 2 : 29 pmol/10 9 cells) [9]. We explain these results by rate-limiting FPGS activity in marrow progenitors rather than saturation of MTX uptake (which is passive at higher dose MTX).…”
Section: Discussionsupporting
confidence: 79%
“…However, HDMTX administration resulted in fourfold higher MTXPG 5 levels (median 9.2 pmol/10 9 cells) by comparison with very longchain MTXPG levels observed during weekly low-dose MTX during maintenance (median MTXPG 5-7 was 2.4 pmol/10 9 cells) [9], and these data are consistent with the greater accumulation of long-chain MTXPG in bone marrow lymphoblasts following higher dose MTX [17]. Moreover, the percentage of very long-chain MTXPG [4][5] (over 40% of the total MTXPG) following HDMTX courses was signiWcantly higher than those reported following maintenance therapy of ALL (i.e., 18% MTXPG 4-5 with a 20 g/m 2 dosage) [9,18]. Altogether, these data support the rational of administering HDMTX to produce longer chain MTXPG which are more potent inhibitors of de novo purine biosynthesis than short-chains MTXPG [17,19].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…2 It was also based on the assumption that MTX, through inhibition of the de novo purine synthesis, increases the levels of phosphoribosyl pyrophosphate, and thereby increases both the build up of 6TGN and their incorporation into DNA, although the latter has not yet been proven in clinical studies. 27 However, it is not known whether uninterrupted maintenance therapy with reduced doses of 6MP is superior to full-dose therapy with intermittent treatment interruptions. A few studies have indicated that reductions of the overall 6MP dose intensity because of treatment interruptions may affect the cure rate.…”
Section: Discussionmentioning
confidence: 99%